Physical environment and the planning of sub-basin of the quebrada de Chucumayo. Application of geomatics Matucana district, Huarochiri province, Lima department - Meléndez de la Cruz, Juan (2017)
The sub basin of the Quebrada de Chucumayo is a contributor of the Rimac River (RR) on its left bank and is framed in morphology of mountains. The contributions of this research are: a) Lifting of new hematic information on geomorphology, vegetation and use capacity Soils, which was the basis for assessing land use and know the natural soil suitability. b) The design and implementation of models to assess the geographic applying each of the ecological economic units on productivity, conservation and land use conflicts approach. c) Identification of spatial units with problems of conflict of Use and disaster risks. d) Ecological and Economic Zoning study area as input geospatial prepare a proposed land uses through a (planning). In summary, we found that most of the economic activities in a situation of unsustainable because they are exposed to the impact of natural hazards spaces corresponding to conflicting land uses.